Analysis of energy and water use in USA farmed catfish: Toward a more resilient and sustainable production system. (15th December 2022) - Viglia, Silvio; Brown, Mark T.; Love, David C.; Fry, Jillian P.; Scroggins, Rachel; Neff, Roni A.
Abstract: Catfish is the largest aquaculture sector in the U.S., and there is no peer-reviewed lifecycle analysis characterizing the sector's environmental footprint. This study estimates energy and water demand per kg of catfish, based on analysis of primary data collected from businesses involved in catfish farming, hatcheries, feed mills, and processing. Further, it describes business operator perceptions of potential strategies to reduce usage. We found that direct energy inputs accounted for 49% of energy usage, while feed production, especially crop production to produce feed ingredients, comprised 39% and indirect inputs comprised 12% of usage. The largest direct energy demand came from pond aeration. Among water uses, direct water inputs, particularly for filling ponds after evaporation and harvesting, comprised the largest share (59%). Water for feed production comprised another 40%. Interviewees discussed current and potential strategies to reduce energy and water use, including automatic aerators with sensors, improved equipment, rainwater capture, and alternative harvesting practices. Shifts in crop production could also reduce catfish embodied resources. Incentives to offset costs would increase adoption. In sum, this study provides the most comprehensive exploration to date of the energy and water footprint of the largest U.S. aquaculture sector and identifies multiple opportunities that could improve the industry's resource use. Highlights: Catfish farming is the largest aquaculture sector in the U.S. We analyzed energy and water intensities of USA catfish aquaculture and processing. Direct energy inputs accounted for 49% and feed 39% of total embodied energy. Direct water inputs accounted for 59% and feed 40% of total embodied water. Catfish has lower energy and water use compared to other U.S. finfish aquaculture.